IMPROVING STUDENTSâ MOTIVATION IN SPEAKING ABILITY BY USING STORY RETELLING - Samsudin, Samsudin; Sukrisno, Alim (English Education Journal, 2016)
Cultural understanding is the core of language acquisation. This study aimed at presenting the cultural elements and cultural types, describing the frequency of cultural elements and cultural types in Englihs textbooks of 2013 currirulum and describing the level of the quality of English textbooks in terms of intercultural awareness. This study employed a qualitative research design. The data are the cultural elements and cultural types in English textbooks of 2013 curriculum grade X, XI and XII. The results show that English textbooks grade X, XI and XII contained 490 cultural elements consisting of 232 products, 75 practices, 11 perspectives and 172 persons. While cultural types contained 490 consisting of 127 source culture, 170 target culture, 64 international target culture and 130 culture free. From the results of the study, it can be concluded that the presentation of cultural elements and cultural types are balanced enough. And third English textbooks are equality to use in terms of basic cultural awareness. Whereas, advanced cultural awareness and intercultural awareness level do not support students to have intercultural awareness. From the results above the authors of English textbooks should put the cultural information explicitly either source culture, target culture, international target culture or culture free as a comparison and contrast between them.